Kidnapped - Brook, Henry; Harvey, Bob (Usborne Publishing Ltd London, 2013)
Rivetingly retold for today's readers, Robert Louis Stevenson's stirring tale of intrigue and adventure in the Scottish Highlands is as fresh and exciting as the day it was first written